Presence, Characteristics, and Prognostic Associations of Carotid Plaque Among People Living With HIV. (October 2017) - Janjua, Sumbal A.; Staziaki, Pedro V.; Szilveszter, Balint; Takx, Richard A.P.; Mayrhofer, Thomas; Hennessy, Orla; Emami, Hamed A.; Park, Jakob; Ivanov, Alexander; Hallett, Travis R.; Lu, Michael T.; Romero, Javier M.; et al.
Abstract : Background—: Data from broad populations have established associations between incidental carotid plaque and vascular events. Among people living with HIV (PLWHIV), the risk of vascular events is increased; however, whether incidental carotid plaque is increased and there is an association between incidental carotid plaque, plaque characteristics, and vascular events among PLWHIV is unclear. Methods and Results—: Data from the multi-institutional Research Patient Data Registry were used. Presence and characteristics (high-risk plaque, including spotty calcification and low attenuation) of carotid plaque by computerized tomography among PLWHIV without known vascular disease were described. Data were compared with uninfected controls similar in age, sex, and cardiovascular risk factors, including diabetes mellitus, hyperlipidemia, and cigarette smoking to cases. Primary outcome was an atherosclerotic cardiovascular disease event, and secondary outcome was ischemic stroke. Cohort consisted of 209 PLWHIV (45±10 years, 72% male) and 168 controls. Using computerized tomography, PLWHIV without vascular disease had higher rates of any carotid plaque (34% versus 25%; P =0.04), noncalcified (18% versus 5%; P <0.001) and high-risk plaque (25% versus 16%; P =0.03). Over a follow-up of 3 years, 19 atherosclerotic cardiovascular disease events (9 strokes) occurred. Carotid plaque was independently associated with a 3-fold increase in atherosclerotic cardiovascular disease events among PLWHIV (hazard ratio, 2.91; confidence interval, 1.10–7.7, P =0.03) and a 4-fold increased risk of stroke (hazard ratio, 4.43; confidence interval, 1.17–16.70; P =0.02); high-risk plaque was associated with a 3-fold increased risk of atherosclerotic cardiovascular disease events and a 4-fold increased risk of stroke. Conclusions—: There is an increase in incidental carotid plaque, noncalcified plaque, and high-risk plaque among PLWHIV, and the presence and characteristics of carotid plaque are associated with subsequent vascular events.